Study of Some Histopathological and Immunological Analysis in Patients with Chronic Tonsillitis - Hetaf Shallal Farhan; Ahmed Sami Farhan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Several histopathological and immunological changes that occur in patients with palatine tonsillitis. Blood and tonsil samples were collected from patients with palatine tonsillitis and (healthy peoples) in Ramadi city. The results of histopathological analysis showed the percent of immunopositive cells for the proliferation marker was low while the percent of immunpositive cells for the apoptosis marker was high. Serum was used to know the effect of palatine tonsillitis on some assays CRP, RF, IL-6 and IgM. The results were showed the following: Significant increase in the levels of CRP and RF in patients compared with control group. Significant increase in the levels of IL-6 and IgM compared with control group. We conclude that patients in Ramadi city have several pathological changes in palatine tonsils.